Mountain View Corridor Protection Urban Design Hefei City Dashu Hill Area - Xiaoxiao Zhang; Jianxiong Yang (Lowland Technology International, 2020)
Dashu Hill is the only mountain in Hefei. The paper analyses the relevant methods of the protection of mountain view corridor and expatiates on the evolution of methods and ideas for the protection of the view corridor within all previous Dashu Hill area urban design. Based on the new problems and technical methods, the design has made some research innovation in the protection of mountain view corridor.